Bilingualism across the lifespan : factors moderating language proficiency - Nicoladis, Elena; Montanari, Simona (Linguist) (Language and the human lifespan series., 2016)
"The study of bilingualism unfolds against a varied backdrop of sociocultural and sociopolitical factors. While the nature of bilingualism and multilingualism has often been misunderstood, the bilingual community is a dynamic and ever-growing part of the global population. This book pioneers the study of bilingualism across the lifespan and in all its diverse forms. In framing the newest research within a lifespan perspective, the editors highlight the importance of considering an individual's age--from infancy to late adulthood--when researching how bilingualism affects language acquisition and cognitive development. A key theme of the volume is the variability among bilinguals, which may be due to a host of individual and sociocultural factors. Five major topics are explored: early bilingualism, factors affecting bilingualism across the lifespan, academic achievement and literacy in bilinguals, and cognitive effects of bilingualism. While bilingualism is not always valued in the U.S. and thus may result in negative outcomes, in other countries and contexts, positive outcomes are common. Thus, this book is a call for language researchers, psychologists, and educators to pursue and promote a better understanding of bilingualism in our increasingly multicultural society"--Publicity materials. (PsycINFO Database Record (c) 2016 APA, all rights reserved)